HUBUNGAN MEKANISME KOPING DENGAN TINGKAT ANSIETAS PADA KLIEN DENGAN PENYAKIT KANKER DI RSPAD GATOT SOEBROTO - Zakiyah Mujahidah; Suwarningsih Soeharto; Tika Silviasari (Universitas Mohammad Husni Thamrin, 2019)
Cancer is a disease caused by abnormal growth of cells of the body tissues will be change the cancer cells. Patients who get cancer will get anxiety or commonly called 'kecemasan'. Anxiety is a feeling of unidentified fear and is not supported by the situation. Anxiety can be handle with coping mechanisms. Coping mechanism have two type, they are namely adaptive coping mechanism and maladaptive coping mechanism. This research using descriptive method with cross sectional approach and chi square test to find corellation between coping mechanism and anxiety level on clients with cancer at RSPAD Gatot Soebroto with 66 respondents. The results of research was held on August 2017 there were (51.5%) patients with maladaptive coping mechanisms and (48.5%) patients with adaptive coping mechanisms. Patients with low anxiety were (16.7%), middle anxiety (62.1%) and heavy anxiety (21.2%) with p-values 0.735 and 0.537, α = 0.05 OR = 0.652 (95% CI 0.171-2.485) and OR = 1.704 (95% CI 0.500-5.800). The conclusion of this research, it is not found the significant correlation between coping mechanisms and anxiety level on clients with cancer at RSPAD Gatot Soebroto . Based on the result of this research showing that is good coping mechanism can be reduce anxiety level on cancer patients. Keywords : Cancer, Anxiety, Coping Mechanism